Analysis of Students’ Error in Solving Problems on SPLDV Material Based on Newman's Theory - Kartini, Kartini; Dian, Monika Putri; Hutapea, Nahor Murani (PRISMA, 2025)
This study aims to analyze students' errors in solving problem-solving problems on the material of two-variable linear equation systems based on Newman's theory. This study needs to be conducted in order to help find out what mistakes students make so that it will be easier to find solutions to minimize the occurrence of these errors in learning. The research method used is descriptive qualitative. The subjects in the study were 16 students of class X MA Cendekia Bangsa. The study was conducted in the 2024/2025 academic year, even semester. The data collection technique used by the researcher was using a test instrument in the form of two essay questions containing indicators of mathematical problem-solving abilities on the material of two-variable linear equation systems and interviews. The results of the analysis of students' errors in solving problem-solving problems on SPLDV material based on Newman's theory obtained 9.4 % reading errors (very low category); 28.1% understanding errors (low category); 40.6% transformation errors (sufficient category); 62.5% process skill errors (high category) and 21.9% answer writing errors (low category). The largest percentage of errors is in processing skills errors which are caused by many students still having problems with algebraic calculations and integer operations.